PERAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SD N JATIRUNGGO 01 - Jaya Yanti Nur Istiqomah; Rina Ardani; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The quality of learning is greatly influenced by the quality of professional teacher performance, therefore efforts to improve the professional ability of teachers in carrying out the learning and teaching process can be through supervision assistance. Teacher professionalism at SD N Jatirunggo 01 can still be said to have not achieved optimal results, therefore through supervision activities the principal provides guidance, motivation and technical assistance to teachers who experience difficulties in learning activities so that they can improve teacher professionalism. The problem that the author formulated is: How is the role of principal supervision in improving teacher professionalism at SD N Jatirunggo 01. The purpose of the study is: To Determine the Role of Principal Supervision in Improving Teacher Professionalism at SD N Jatirunggo 01. This study is a descriptive quantitative study that aims to create a description, a systematic, factual and accurate picture of the facts, characteristics and relationships between the phenomena being investigated. Data can be obtained through observation, interviews and documentation. When all the data has been collected, it is then analyzed using data analysis consisting of the stages of data reduction, data presentation, and verification. Based on the results of this study, it shows that the role of the principal's supervision in improving teacher professionalism at SD N Jatirunggo 01 has been attempted to achieve optimal results. The aspects of the role of supervision carried out by the principal are by (1) coordinator, (2) consultant, (3) group leader, and (4) evaluator. The achievement of all aspects of supervision is categorized as good. Teacher professionalism at SD N Jatirunggo 01 is categorized as good. The achievement of the pedagogical aspect is categorized as good, the personality aspect is categorized as very good, the social aspect is categorized as very good, and the professional aspect is categorized as good. The implementation of supervision should be further improved, carried out routinely and continuously and efforts should be made so that each teacher receives supervision and socialization regarding the importance of supervision for each teacher to foster awareness in each teacher of the importance of supervKeywords: study 1, profesionalisme 2, teacher 3